A selective review of research on Prostephanus truncatus (Horn) (Col.: Bostrichidae) with an annotated and updated bibliography - Markham, R.H.; Wright, V.F.; Ríos Ibarra, R.M. (1991)
A review is presented of worldwide research on the stored products pest Prostephanus truncatus, with an emphasis on recent (post-1986) and previously neglected work, particularly that published in languages other than English. Topics reviewed include distribution, pest status, biology, ecology, monitoring and control. An annotated bibliography is included.